Carbon dioxide reduction by mixed and pure cultures in microbial electrosynthesis using an assembly of graphite felt and stainless steel as a cathode - Bajracharya, Suman; ter Heijne, Annemiek; Dominguez Benetton, Xochitl; Vanbroekhoven, Karolien; Buisman, Cees J.N.; Strik, David P.B.T.B.; Pant, Deepak (Bioresource technology, 2015)
[Display omitted] •Stainless steel and graphite felt assembly as a CO2 reducing biocathode material.•Higher acetate production rates from C. ljungdahlii with hydrogen evolution.•CH4 production predominated from CO2 reduction by non-enriched mixed culture.•H2 evolution appears to stimulate planktonic bacteria rather than cathodic-biofilm. Carbon dioxide (CO2) reduction to multi-carbon compounds at the cathode using chemolithoautotrophs is an emerging application of microbial electrosynthesis (MES). In this study, CO2 reduction in MES was investigated at hydrogen evolving potentials, separately by a mixed culture and Clostridium ljungdahlii, using a graphite felt and stainless steel assembly as cathode. The mixed culture reactor produced acetate at the maximum rate of 1.3mMd−1, along with methane and hydrogen at −1.1V/Ag/AgCl. Over 160days of run-time in four fed-batches, 26% of bicarbonate was converted to acetate between day 28 and 41, whereas in the late batches, methane production prevailed. Out of 45days of run-time in the C. ljungdahlii reactor, 2.4mMd−1 acetate production was achieved at −0.9V/Ag/AgCl in Batch 1. Simultaneous product degradation occurred when the mixed culture was not selectively enriched. Hydrogen evolution is potentially the rapid way of transferring electrons to the biocatalysts for higher bioproduction rates.